The gut microbiome dysbiosis and its potential role in psoriatic arthritis. (December 2014) - Eppinga, Hester; Thio, Hok Bing; Peppelenbosch, Maikel P; Konstantinov, Sergey R
In past decades, gut microbiome perturbations appeared to play a role in the development of several autoimmune diseases. Microbiome dysbiosis together with genetic, lifestyle and/or diet factors may composedly affect the etiology of autoimmune diseases. Studies about the role of the gut microbiome in psoriatic arthritis (PsA), a chronic autoimmune disease of the joint, are limited. We propose that intestinal dysbiosis-associated microbiota or gut microbiota-derived products might reach the joint by translocation to the circulation leading to T-cell activation and inflammation that underline PsA. Future studies on the intestinal microbiome associated with psoriatic arthritis can provide new targets for diagnostic and treatment strategies. Recognizing the PsA 'early warning phases' could offer new windows of opportunities regarding prevention.